Energy Recovery from Byproduct of Sugar Cane Processing Plant: Review Articles - Awulachew, Melaku Tafese (International Journal For Research In Agricultural And Food Science, 2020)
The energy crisis necessitates studying and discovering new processes involved in the production of utilizable compounds as alternative energy sources among which fermentation to ethanol represents a significant strategy. The aim of this material was to assist processors to understand and apply the energy generation from sugar processing plant by products; to address that, there exists an increased unit production cost of sugar unless otherwise simultaneous production of diversified products stipulated from the same sugar cane source and the redetermination of the initial sugar concentration and amount of yeast to optimize the molasses medium. Sugarcane resource can be used to produce a variety of commercial products that can be marketed domestically, regionally and internationally. In economic and environmental terms, the three products that have special significance area sugar, ethanol, and electricity. Ethiopia through its potential in developing large sugarcane production can play a pro-active role in mitigating the same. Molasses the non-crystallizable residue remaining after crystallizing sucrose, has additional advantage; it is relatively inexpensive raw material, readily available and already in use for industrial ethanol production. Along with sugar production, diversification was considered to include ethanol production and electric cogenerations.